2021
DOI: 10.1007/s40544-021-0502-8
|View full text |Cite
|
Sign up to set email alerts
|

Drag reduction methods at solid-liquid interfaces

Abstract: Friction drag is a nonnegligible matter when relative motion happens between solid and liquid phase, which brings many inconveniences in ship navigation, fluid transportation, microfluid devices, etc. Thereby various methods have been developed focusing on friction drag reduction. In this article, a review of several widely studied drag reduction methods is given, specially, their advantages and limitations in practical applications are discussed. Besides, a comparison of different methods is made and the deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 194 publications
(236 reference statements)
0
14
0
Order By: Relevance
“…In this study, the drag reduction of our artificial sharkskin was demonstrated by the synergistic effects originating from the riblet-textured geometry of the microdenticles and the hydrophobic wetting property of the PDMS-based materials (Figure 3a-e). Hydrophobic surfaces have been studied to reduce drag by air retention, even under laminar flows [36,37] with a low Reynolds number. The drag reduction was attributed to water slipping on the surface with air, which has a lower density than that of water.…”
Section: Demonstration Of Drag Reduction On 3d Artificial Sharkskinmentioning
confidence: 99%
“…In this study, the drag reduction of our artificial sharkskin was demonstrated by the synergistic effects originating from the riblet-textured geometry of the microdenticles and the hydrophobic wetting property of the PDMS-based materials (Figure 3a-e). Hydrophobic surfaces have been studied to reduce drag by air retention, even under laminar flows [36,37] with a low Reynolds number. The drag reduction was attributed to water slipping on the surface with air, which has a lower density than that of water.…”
Section: Demonstration Of Drag Reduction On 3d Artificial Sharkskinmentioning
confidence: 99%
“…Therefore, it was beneficial to design the composite surface with DR and antifouling abilities . Natural creatures evolving unique structures and excellent surface functions through millions of years of natural selection could adapt to the harshest environment. Inspired by natural creatures, scientists and engineers have obtained many innovative inspirations to address the above technical challenges. Numerous studies have indicated that many tiny denticles embedded in the shark skin and parallel to the streamwise direction played a decisive role in reducing drag and antifouling. …”
Section: Introductionmentioning
confidence: 99%
“…[ 7–12 ] Therefore, the superhydrophobic films demonstrate essential practical values in aircraft flight, ship navigation, and chemical production, which also brought practical improvements in safety, economy, and convenience. [ 13–15 ]…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11][12] Therefore, the superhydrophobic films demonstrate essential practical values in aircraft flight, ship navigation, and chemical production, which also brought practical improvements in safety, economy, and convenience. [13][14][15] It is well known that the preparation of superhydrophobic surfaces can be summarized in two ways: constructing micronanostructures on the surface of materials with inherent hydrophobicity or constructing micro-nanostructures on the surface of hydrophilic materials while reducing their surface energy. [16] Most common metals and alloys in daily life are hydrophilic substances, thus it is not only necessary to construct micro-nanostructures on their surfaces but also to reduce their surface energy to obtain superhydrophobic coatings.…”
mentioning
confidence: 99%